2016
DOI: 10.1614/wt-d-15-00149.1
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Tolerance to Bed-Top and Drip-Applied Preemergence Herbicides

Abstract: Broadleaf weeds and nutsedge are persistent problems with limited management options for strawberry growers in Florida. Experiments were conducted in 2012 to 2013 (year 1) and 2013 to 2014 (year 2) at the Gulf Coast Research and Education Center in Wimauma, FL, to evaluate tolerance of two strawberry cultivars (‘Strawberry Festival' and ‘WinterStar'™) to PRE herbicides applied on the bed top or injected through the drip tape. The bed-top herbicides were applied to formed beds following fumigation but prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…In previous research, Boyd and Reed (2016) reported EPTC at 229 and 458 g ha , fomesafen at 42 and 84 g ha , and oxyfluorfen plus S-metolachlor at 56 + 448 g ha −1 applied through drip irrigation at 1, 7, 15, and 30 d prior to transplanting did not cause significant strawberry injury. Daugovish et al (2008) also found oxyfluorfen applications made 7 d prior to transplanting did not injure strawberry.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In previous research, Boyd and Reed (2016) reported EPTC at 229 and 458 g ha , fomesafen at 42 and 84 g ha , and oxyfluorfen plus S-metolachlor at 56 + 448 g ha −1 applied through drip irrigation at 1, 7, 15, and 30 d prior to transplanting did not cause significant strawberry injury. Daugovish et al (2008) also found oxyfluorfen applications made 7 d prior to transplanting did not injure strawberry.…”
Section: Resultsmentioning
confidence: 77%
“…Gilreath et al (2003) reported that napropamide plus oxyfluorfen at 4.5 + 0.57 kg ha −1 resulted in the best grass and broadleaf weed control and also had greater berry numbers and weights than did either herbicide applied alone. Boyd and Reed (2016) reported that EPTC at 458 g ha…”
mentioning
confidence: 99%
“…Strawberry yields in the non‐fumigated control were comparable with the soil fumigated with 1,3‐D + Pic or EDN. This is likely due to insufficient weed or soil‐borne disease pressure to reduce yields …”
Section: Discussionmentioning
confidence: 99%
“…A number of pre‐emergent (PRE) herbicides have been evaluated for use in strawberry . Previous studies demonstrated strawberry tolerance to PRE applications of S‐ethyl dipropylthiocarbamate (EPTC), fomesafen, pendimethalin, prodiamine, napropamide and oxyfluorfen . However, control of weeds with these PRE herbicides in strawberry has been inadequate or inconsistent .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation